Life beyond Refuge: A System Theory of Change for Supporting Refugee Newcomers - Janzen, Rich; Taylor, Mischa; Gokiert, Rebecca (Refuge, 2022)
Canada is internationally recognized as a leader in welcoming refugee newcomers. However, there is limited evidence about how well refugee newcomers fare after arriving in Canada, and the effectiveness of resettlement services and supports. A system theory of change was developed to guide assessments of complexity across the refugee-serving sector that seek to investigate refugees’ lived experiences and evaluate practice across multiple levels. This article describes the process of developing the system theory of change, Life Beyond Refuge, and the implications for community-level practice, public policy, and ultimately, resettlement outcomes for refugee newcomers.